A Review of Emerging Evidence for Utilization of a Percutaneous Interspinous Process Decompression Device to Treat Symptomatic Lumbar Adjacent-Segment Degeneration. Issue 2 (6th December 2019) - Deer, Timothy R; Sayed, Dawood; Malinowski, Mark N; Rowe, Jeffery J; Jameson, Jessica B; Liang, Kevin; Sclafani, Joseph A
Abstract: Objective: Postlaminectomy syndrome diagnoses secondary to adjacent segment degeneration are a substantial and rising cause of morbidity in the United States. Emerging spinal cord neuromodulation technologies have produced successful outcomes for postlaminectomy neuropathic pain but are less effective in treating neurogenic claudication secondary to recurrent lumbar stenosis. Percutaneous interspinous process decompression systems can be used as a salvage treatment modality for persistent structural neurogenic claudication in postlaminectomy syndrome or after spinal cord stimulator implantation. Methods: This paper is a review of emerging evidence for efficacious utilization of percutaneous interspinous process decompression. Results: A recent pragmatic trial of subjects who underwent percutaneous interspinous process decompression for lumbar stenosis with intermittent neurogenic claudication reported that 63% (26/41) maintained minimal clinically important improvement in visual analog scale (VAS) leg pain, 61% (25/41) in VAS back pain, 78% (32/41) in function objective values, and 88% (36/41) reported satisfaction with treatment at 12 months postop. All subjects in a small case series of seven individuals with postlaminectomy adjacent-segment disease reported postoperative satisfaction scores of 3 or 4 on a 0–4 scale and were also able to decrease or wean completely off controlled pain medications. In another study, there was a significant decrease in average leg pain (60% improvement, P  < 0.0001, N = 25) and axial low back pain (58% improvement, P  < 0.0001, N = 25) in patients who underwent one- or two-level percutaneous interspinous process decompression as a rescue treatment for reemerging neurogenic claudication after spinal cord stimulator implantation. Conclusions: The spine often is a focus of progressive disease. Furthermore, mechanical changes associated with spinal instrumentation can lead to additional disease at adjacent levels. Many individuals will present with symptomatic neurogenic claudication recalcitrant to multimodal management strategies, including even the most sophisticated neuromodulation technologies. Implementation of salvage percutaneous interspinus process decompression implantation in cases of adjacent segment degeneration or incomplete spinal cord stimulation can decompress structural causes of neurogenic claudication while sparing the patient from more invasive surgical reoperation techniques.